STABILITAS FISIK EMULGEL MELOKSIKAM MENGGUNAKAN METODE FREEZE THAW - ASA FALAHI (AKADEMI FARMASI JEMBER, 2021)
Emulgel is a semi-solid preparation, in the form of an emulsion where the viscosity is increased by the addition of the gelling agent. Emulgel can be used for formulations of active substances that are difficult to dissolve in water. Meloxicam is a first-line treatment to treat rheumatoid arthritis and osteoarthritis. The aim of the study was determine the stability of the physical properties of emulgel meloxicam with the Freeze thaw test. The research design used was quasi experimental. In this study there were 2 storage temperatures, the freeze temperature of 4-8oC and thaw temperature of 40-48oC. The treatment was carried out in 3 cycles for 6 days. Physical stability test of organoleptic (color, odor, and dosage form) showed no difference during storage. Physical stability test of homogenity also showed no difference during storage. Physical stability of the emulsion type showed that there was no phase separation in the emulsifying gel during storage. Significance of pH is 0,083 (p 0,05), viscosity is 0,083 (p0,05), and spreadabilityis 0,102 (p 0,05) can be interpreted that the physical stability of pH, viscosity and dispersion power has no significant difference. From all research data, it can be seen that the meloxicam emulgel preparation did notchanges in physical stability after passing 3 cycles.